Regulation of oxidative stress resistance in Campylobacter jejuni, a microaerophilic foodborne pathogen - Kim, Jong-Chul; Oh, Euna; Kim, Jinyong; Jeon, Byeonghwa (Frontiers in Microbiology, 2015)
Campylobacter jejuni is one of the leading bacterial causes of human gastroenteritis. Due to the increasing rates of human campylobacteriosis, C. jejuni is considered as a serious public health concern worldwide. C. jejuni is a microaerophilic, fastidious bacterium. C. jejuni must overcome a wide range of stress conditions during foodborne transmission to humans, such as food preservation and processing conditions, and even in infection of the gastrointestinal tracts of humans. Particularly, this microaerophilic foodborne pathogen must survive in the atmospheric conditions prior to the initiation of infection. C. jejuni possesses unique regulatory mechanisms for oxidative stress resistance. Lacking OxyR and SoxRS that are highly conserved in other Gram-negative foodborne pathogens, C. jejuni modulates the expression of genes involved in oxidative stress resistance mainly via the PerR and CosR regulators. Based on recent findings of ours and others, in this review, we described how C. jejuni regulates the expression of oxidative stress defense.